Relativism in Context - Laera, Rodrigo (Aufklärung: journal of philosophy, 2019)
The present paper introduces four fundamental issues within the framework of epistemic relativism: (a) the lack of precision in the concept of knowing; (b) the changes in the demands between context of use and of evaluation; (c) the violation of the real disagreement intuition; and (d) the incommensurability of epistemic frameworks. The answer to these problems should revolve around the idea that knowledge is subject to the interests and intentions of individuals in everyday life. The main thesis thus consists in that it is necessary to avoid the impression that epistemic frameworks are some sort of watertight compartment. In this way, relativism may be defended from the viewpoint that epistemic frameworks are artificial generalizations that may be relevant to the attribution of knowledge. In this respect, it must be borne in mind that some norms are shared by different epistemic frameworks, and that each time a given context or circumstance takes place, the same norm may be applied.